Investigation Of Turning Results Using Used Chisel Bit File And Ahisel Bits From ST-37 Steel Pack Carburizing - Wijayanto, Hendi Lilih; Malau, Alexander; Amiruddin, Amiruddin; Putra, Aditya Perdana; Alfian, Muh (Politeknik Negeri Lhokseumawe, 2024)
Much research in the manufacturing industry has been conducted on variations in cutting force, temperature, and chip directly related to tool wear and cutting performance. Therefore, this research analyzed the cutting performance of cutting tools from the pack carburizing-used files against the results of turning facings. Then, the chisels were welded to ISO 6 tool holders after welding. The chisels were used to turn low carbon steel ST-37 with a diameter of 50.4 mm using a timeway CL-460 lathe with 0.2mm feeding and 400, 605, 910, and 1330 RPM variations. The test results indicated that the bit of carbide from the pack carburizing had a roughness value of 0.890 µm, belonging to class N6. Hence, the roughness value was lower (smoother) than turning facing using a file used from pack carburizing with a roughness value of 3.014 µm.